Analisis Perubahan Ketiga Undang-Undang Mahkamah Konstitusi Ditinjau dari Perspektif Pembentukan Peraturan Perundang-Undangan Di Indonesia - Ahmad Yusup (Ajudikasi : Jurnal Ilmu Hukum, 2022)
The third amendment to the Constitutional Court Act drew a lot of criticism, especially regarding the urgency of the change, considering that the Constitutional Court Law is not included in the priority prolegnas in 2020. There are two issues of the third amendment to the Constitutional Court Law that are highlighted in this article, namely, The Material Analysis of the Third Amendment to the Constitutional Court Law is based on the Regulation on the Formation of Laws and Regulations and the Formal Analysis of the Third Amendment to the Constitutional Court Law In terms of the Law on the Formation of Laws and Regulations. The research method used is a type of normative research. The approaches used in this study are the statute approach, case approach and concept approach using prescriptive analysis. The results of the analysis show that (1) Materially, the Third Amendment to the Constitutional Court Law is based on the Regulation on the Establishment of Laws and Regulations, it is noted that the Third Amendment to the Constitutional Court Law has defects in its amendments, namely regarding the minimum limit of age to be able to become a constitutional judge and regarding the abolition of the period of periodization of constitutional judges which is considered contrary to the constitution or unconstitutional. and (2) Formally, the Third Amendment to the Constitutional Court Law In view of the Law on the Establishment of Laws and Regulations of the Constitutional Court Law, the third amendment has been formally flawed in its amendments, where there are several provisions that are not in accordance with the format of preparation as intended in Law Number 12 of 2011 jo Law Number 15 of 2019 concerning the Establishment of Laws and Regulations (P3 Law).